Clock Walking and Gender: How Circular Movements Influence Arithmetic Calculations - Lugli, Luisa; D’Ascenzo, Stefania; Borghi, Anna M.; Nicoletti, Roberto (Frontiers in Psychology, 2018)
Starting from a rich body of evidence on the strict bi-directional relationship between numerical cognition and action processes, the present study aims at deepening the knowledge about the influence of the body movement on arithmetic calculation. Numerous studies have shown that moving the body along the vertical or the horizontal axis could facilitate the calculation of additions and subtractions. More specifically, results showed an effect of congruence between the type of operation (additions vs. subtractions) and the direction of the movement performed (up / right or down / left). While this congruence effect is present for both additions and subtractions when the axis of action is vertical, when the axis of action is horizontal the effect appears only for additions. The purpose of this study is to investigate the influence of circular motion, which has so far not been explored, on counting. Participants were asked to count by adding or subtracting 'three' while performing a circular motion (i.e., a clockwise or counterclockwise movement), in an active (i.e. walking) or passive mode (i.e. being pushed on a wheelchair). Results showed a congruence effect for additions calculated in the active modality and only for male participants. Implications of the results for theories of embodied cognition and for the debate on gender differences in mathematical skills are discussed.